Harnessing the Power of Interpersonal Communication and Work Ethic to Drive Employee Performance - Maulana Ismail; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Interpersonal communication is an important aspect in an organization to manage the flow of information between employees or employees and superiors, while work ethic plays an important role in increasing motivation and commitment in carrying out tasks, an ammonia distribution company in Karawang. The research background shows that the performance of employees of this company is still not optimal, with data showing fluctuations in performance scores from 2021 to 2023. The study aims to evaluate the extent to which interpersonal communication and work ethic contribute to improving employee performance. The methodology used is a quantitative verification approach with a population of 34 employees, using a closed questionnaire as a data collection instrument. The results showed that interpersonal communication has no significant effect partially on employee performance, while work ethic has a significant effect. Simultaneously, the two variables contributed 80.6% to the variation in employee performance. This finding confirms the importance of work ethic development as a top priority to improve productivity and work quality. In conclusion, although interpersonal communication has no significant effect partially, the synergy between good interpersonal communication and high work ethic together can create a more effective and harmonious work environment. Recommendations for management are to strengthen communication training and work ethic development programs to optimize employee performance.